(untitled) (Journal of Contemporary Issues in Accounting, 2024)
The study ascertained the effect of public external debt on economic development in Nigeria for the period of 1981 to 2023. The multiple regression technique of analysis was employed and the data for the variables such as nominal gross domestic product, total external debt, multilateral debt and bilateral debt were sourced from Central Bank of Nigeria Statistical Bulletin. The Johansen cointegration test revealed a long run relationship among the variables and the result of the multiple regression carried out however showed that total external debt has negative but significant impact on economic development, while multilateral debt has positive and significant effect on economic development. Similarly, bilateral debt has positive but insignificant effect on economic development. Based on the findings of the study, the study recommends that government should monitor and efficiently utilize the funds borrowed from external sources for capital projects, as this would accelerate the development of Nigeria economy.